Thermal decomposition of magnesium carbonate with biomass and plastic wastes for simultaneous production of hydrogen and carbon avoidance. (10th February 2018) - Devasahayam, Sheila; Strezov, Vladimir
Abstract: Application of biomass and waste plastics as resources for production of hydrogen enables sustainability of the chemical industry. In this step change novel carbon avoidance method, the carbon dioxide produced in a high carbon footprint process is consumed by thermal processing of magnesium carbonate in presence of biomass and plastics, simultaneously producing hydrogen. This study details the thermal decomposition of magnesium carbonate in presence of epoxy resin and biomass, as a renewable resource, at 1000 °C. The epoxy resin of known composition was used as a representative of the waste plastics as well as bio-renewable resource. Significant increase in carbon dioxide avoidance potential of up to 99% is realised in this work. The study promises significant reduction in current reaction temperature (∼1600 °C) for the dead burnt magnesium oxide production and magnesium production via carbothermic reduction of magnesium oxide attributed to the reducing atmosphere presented by hydrogen when biomass and waste plastics are used in the process. This study establishes the conditions for carbon dioxide avoidance, hydrogen enrichment and methane enrichment by merely controlling the ratios of the magnesium carbonate, biomass and epoxies. Highlights: The study presents step change carbon avoidance of high carbon footprint process. This study demonstrates 99% carbon avoidance using biomass and plastic wastes. This process is accompanied by H2 enriched by-product. Potential reduction in process temperature and toxic emissions is presented. This process reduces landfilled wastes promoting dematerialization.